A Clean Fight: Comparing Metronidazole and Silver Sulfadiazine Gels in Treating Infected Diabetic Foot Ulcers: A Randomized Control Trial - Romano, Giulia; More, Claire; Garnier, Élodie; Fernández Navarro, Lucía; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2025)
Background: Diabetic foot ulcers (DFUs) are a major cause of morbidity and non-traumatic amputations among patients with diabetes. Infection delays healing and increases the risk of severe complications, underscoring the need for effective topical treatments. Objective: To compare the efficacy of topical Metronidazole versus Silver Sulfadiazine (SSD) in promoting wound healing in infected DFUs, and to evaluate the influence of systemic markers, including HbA1c, CRP, and albumin, on treatment outcomes. Methods: This randomized, double-blind controlled trial was conducted at the Centre Médical de Saint-Jean-sur-Veyle from April to June 2025. Ninety adult patients with mild-to-moderate infected DFUs were randomly assigned to either Metronidazole or SSD. Patients with severe infection, osteomyelitis, or severe ischemia were excluded. Participants received daily topical application of either 1% Metronidazole or 1% SSD gel for four weeks, alongside standard care including debridement, offloading, and glycemic control. The primary outcome was complete wound healing at 4 weeks. Secondary outcomes included wound size reduction, time to healing, and changes in infection severity scores. Subgroup analyses assessed the impact of clinical covariates on healing. Results: Among 90 participants, 86 completed the trial. The Metronidazole group had a significantly higher healing rate (86.7%) compared with the SSD group (68.9%; p = 0.011). ANCOVA showed a significant treatment effect on wound size (F = 6.89; p = 0.011). GEE analysis identified a significant time-by-treatment interaction (OR = 3.06; p = 0.002). Poor healing was associated with wound size ≥5 cm², HbA1c ≥8%, CRP ≥10 mg/L, and albumin <3.5 g/dL. Conclusions and Relevance: Metronidazole was more effective than SSD in promoting short-term wound healing in infected DFUs. It may be considered a preferred topical agent, especially in settings with high anaerobic burden and limited resources.